A road for macroporous silicon stabilization by ultrathin ALD TiO2 coating - Al Chimali, Bachar; Carrasco, Irene; Defforge, Thomas; Dailleau, Romain; Monier, Lisa; Baishya, Kaushik; Macák, Jan; Gautier, Gael; Le Borgne, Brice (ROYAL SOC CHEMISTRY, 2024)
Macroporous silicon films have great potential for a plethora of applications in optoelectronics and microelectronics. However, such layers are too electrically and chemically unstable to be used in fuel cells, supercapacitors or any devices requiring the use of an electrolyte. This is due to their high surface-to-volume ratio, which makes them prone to chemical reactions, such as photo-oxidation, especially in aqueous media. In this work, we investigated how to exploit the capabilities of macroporous silicon while avoiding its oxidation. To do so, we explored the influence of ultrathin TiO2 films by atomic layer deposition (ALD) onto the walls of silicon macropores, created by electrochemical etching from n-type wafers. Using microscopy and optical analysis, we demonstrate the achievability of ALD coating on macroporous silicon, as well as the stability of these films against oxidation. In particular, we show that 5 ALD cycles that correspond to less than 1 nm thin coating are sufficient to passivate the silicon surface. The coated and uncoated layers were analyzed and compared before and after exposure to water and sunlight. The monitoring of the Si-O-Si band area evolution over 29 days gave no evidence of photo-corrosion. In addition, the wettability of the samples did not change after functionalization. Finally, to investigate the oxidation prevention for photocatalytic applications, we showed that methylene blue degradation rates were significantly increased (by 50% on average) for 10 nm TiO2 ALD-coated porous silicon samples when compared to natural degradation. Interestingly, layers thinner than 1 nm also showed enhanced catalytic kinetics for short times (t < 40 min).

Macroporous silicon films have great potential for a plethora of applications in optoelectronics and microelectronics. However, such layers are too electrically and chemically unstable to be used in fuel cells, supercapacitors or any devices requiring the use of an electrolyte. This is due to their high surface-to-volume ratio, which makes them prone to chemical reactions, such as photo-oxidation, especially in aqueous media. In this work, we investigated how to exploit the capabilities of macroporous silicon while avoiding its oxidation. To do so, we explored the influence of ultrathin TiO2 films by atomic layer deposition (ALD) onto the walls of silicon macropores, created by electrochemical etching from n-type wafers. Using microscopy and optical analysis, we demonstrate the achievability of ALD coating on macroporous silicon, as well as the stability of these films against oxidation. In particular, we show that 5 ALD cycles that correspond to less than 1 nm thin coating are sufficient to passivate the silicon surface. The coated and uncoated layers were analyzed and compared before and after exposure to water and sunlight. The monitoring of the Si-O-Si band area evolution over 29 days gave no evidence of photo-corrosion. In addition, the wettability of the samples did not change after functionalization. Finally, to investigate the oxidation prevention for photocatalytic applications, we showed that methylene blue degradation rates were significantly increased (by 50% on average) for 10 nm TiO2 ALD-coated porous silicon samples when compared to natural degradation. Interestingly, layers thinner than 1 nm also showed enhanced catalytic kinetics for short times (t < 40 min).
A road for macroporous silicon stabilization by ultrathin ALD TiO2 coating
Keywords: ATOMIC LAYER DEPOSITION; POROUS SILICON; MESOPOROUS SILICON; SURFACE; METAL; FILMS; WATER; OXIDE; OXIDATION; ANATASE; ATOMIC LAYER DEPOSITION; POROUS SILICON; MESOPOROUS SILICON; SURFACE; METAL; FILMS; WATER; OXIDE; OXIDATION; ANATASE